Effective Facilitation and Major Improvements through Revamping Wage Regulations in Indonesia: Fasilitasi yang Efektif dan Perbaikan Utama melalui Pembenahan Regulasi Pengupahan di Indonesia - Evendi , Zakaria; Fitria Agustina, Isna (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of the Sidoarjo Regency Manpower Office in determining the Regency/City Minimum Wage (UMK). Using a qualitative approach, data were collected through interviews, observations, and documentation with key informants such as workers' unions, employers, and government officials. The findings reveal that the Manpower Office effectively facilitates wage determination by providing necessary infrastructure, forming wage councils, and aligning with central government regulations. However, improvements in infrastructure efficiency and the development of clearer, faster regulatory methods are needed. This research highlights the office's strengths and areas for enhancement in setting fair minimum wages. Highlights: Effective Facilitation: Provides infrastructure and forms wage councils for UMK determination. Regulatory Alignment: Complies with central government policies and living needs. Infrastructure Improvement: Enhances efficiency and develops faster, clearer regulations. Keywords: Sidoarjo Regency, Manpower Office, Minimum Wage, Labor Regulation, Qualitative Research